Estudo dos mecanismos envolvidos no efeito do bisfosfonato alendronato dissódico na doença periodontal experimental - Menezes, Adriana Magalhães Andrade de (2003)
Periodontitis, the major cause of teeth loss in adults, is an inflammatory disease in which occurs alveolar bone resorption and collagen fibers destruction. Bacteria and host factors are necessary to the development of this pathology. Bisphosphonates are a new class of drugs that inhibit bone resorbtion by causing morphological alterations or death of osteoclasts. The objetive of this study is to investigate the effect of the bisphosphonate Dissodic Alendronate (DA) in periodontitis, comparing it with the doxicicline (DX), treatment currently used. Periodontitis was induced by a nylon thread ligature surgically placed around the cervix of the second left maxillary molars of female Wistar rats. Animals were treated with DA (0.25 mg/kg, s.c.) 30 minutes before periodontits induction and daily until sacrifice on 11th day (preventive group). Additionally, saline, DA or DX (5 or 10 mg/kg) were injected s.c. from 5th day and daily up to the 11th day of periodontal disease (curative treatment). The parameters analysed were alveolar bone loss (ABL), histopathologic and microbiological analysis, immunohistochemistry, myeloperoxidase (MPO), neutrophil migration, leukogram measured before and after challenge (6h and 1, 7 and 11 days) and body mass variation. AD, as curative or preventive treatment, reduced this alveolar bone loss similar DX. Histopatologically, the periodontium of animals treated with DA showed preservation of alveolar bone, cementum and collagen fibers of periodontal ligament, and reduced neutrophilic and mononuclear cell infiltrate. This effect on neutrophilic infiltrate was confirmed by MPO and in model of peritonitis induced by carrageenan. In imunohistochemistry, there was marked reduction of immunostaining for TNF in the group treated with DA compared to the saline group. In microbiologic analysis, DA inhibited the growth of bacteria involved in periodontitis. DA increased body mass compared to saline group. These results support clinical testing of bisphosphonates in the treatment of periodontal disease.